PERANCANGAN SISTEM INFORMASI PERCETAKAN (SICETAK) PADA PT MYID PRINT INDONESIA - M Salman Alfsrisi; Ary, Maxsi (Universitas Majalengka, 2024)
PT MYID Print Indonesia faces challenges in compiling and presenting order data information in a transparent, easy, fast, and integrated manner. This research aims to design and implement a web-based printing information system to improve efficiency and accuracy in order data management and financial reporting.The approach used includes gathering relevant literature, interviewing company staff, and observing the order recording and financial reporting processes. The research methodology follows the Waterfall model, which includes requirements analysis, system design, implementation, and testing. The information system developed uses PHP, Laravel, and MySQL technologies.The research results show that the implemented information system can speed up and simplify the process of recording order data and financial reporting. This system also increases information transparency and allows easier access for all related parties. With this system, PT MYID Print Indonesia can support better decision-making and improve overall business performance.